Respuesta :

KGYT

Answer:

(x, y) = (-1, 0)

Step-by-step explanation:

Here:

1. -x + y = 1

2. 2x + y = -2

so just temporarily....

multiply #1 by 2

and

multiply #2 by 2

1. -2x + 2y = 2

2. 4x + 2y = -4            then subtract top from bottom.

   -6x + 0  = 6

          -6x = 6

             x  = -1

Then implement x = -1 into the original state of #2

2. 2(-1) + y = -2

      -2 + y = -2

             y = -2 + 2

             y = 0

(x, y) = (-1, 0)

WooHoo! pls brainliest ;) !

ACCESS MORE